2013
DOI: 10.1002/chem.201204373
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of trans‐β‐Lactams by a Kinugasa Reaction on Water

Abstract: The asymmetric Kinugasa reaction was performed on pure water for the first time without the need for any organic co-solvents. In contrast to most asymmetric Kinugasa reactions, trans-β-lactams were obtained as the major products in good yields, enantioselectivities, and diastereoselectivities (up to 90 % yield, 98 % ee, and >99:1 d.r.). This reaction is atom-economical, environmentally friendly, and affords synthetically useful but challenging products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 117 publications
1
34
0
Order By: Relevance
“…CuAAC reactions, 53 groups of Tang, 55 Evans, 57 Otani 54 and Feng 58 54 Another explanation is also possible: copper(II) salts may be contaminated with Cu(0) and, therefore, the reaction can be catalyzed by Cu(I) ion supplied by the elemental copper acting as a reducing agent. This type of activation is well known in the case of CuAAC reaction, where copper metal (wire or turnings) is often used.…”
Section: Catalysts and Ligandsmentioning
confidence: 96%
See 2 more Smart Citations
“…CuAAC reactions, 53 groups of Tang, 55 Evans, 57 Otani 54 and Feng 58 54 Another explanation is also possible: copper(II) salts may be contaminated with Cu(0) and, therefore, the reaction can be catalyzed by Cu(I) ion supplied by the elemental copper acting as a reducing agent. This type of activation is well known in the case of CuAAC reaction, where copper metal (wire or turnings) is often used.…”
Section: Catalysts and Ligandsmentioning
confidence: 96%
“…Feng et al 58 demonstrated that Kinugasa reaction can be performed efficiently under so-called "on water" conditions.…”
Section: Catalysts and Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the substrate scope is still limited. In particular, the intermolecular asymmetric Kinugasa reaction of alkylacetylenes producing chiral β‐lactams having an alkyl side‐chain at the carbonyl α‐position (C3) remains underdeveloped . This is an important issue because most β‐lactam drug compounds have an alkyl pendant at this position (Figure ) .…”
Section: Figurementioning
confidence: 99%
“…Feasibility of epimerization at the alkylated C3 position to allow cis ‐to‐ trans isomerization was examined with KO t Bu as a base for representative 3‐alkyl‐β‐lactams in a cis / trans mixture (eq 1). These reactions gave diastereomerically pure trans ‐β‐lactams with high enantiomeric purities, confirming the stereochemical course leading to the trans isomers (Tables S5–.…”
Section: Figurementioning
confidence: 99%